The last rose - Cypess, Leah (Cypess, Leah. Sisters ever after, 2023)
"The fourth book in the Sisters Ever After series of fairy tale retellings, this is the wild story of Mera, the only one who can save her beautiful older sister when she is kidnapped by the Beast who viciously rules over their small village"--